The Neutral Theory (Theory of Genetic Drift) and the Nearly Neutral Theory of Molecular Evolution are Opposite to Evolution - Ahad, Md. Abdul (International Journal of Bio-resource and Stress Management, 2023)
The Neutral theory (also known as the theory of genetic drift) means genetic drift and vice-versa. But the Nearly Neutral theory means genetic drift plus natural selection. However, genetic drift changes the gene frequency randomly and thus it is non-additive, directionless and thus valueless for evolution. Again, genetic drift works only in small populations and thus, genetic drift means small population. But small populations have to inbreed and produce homozygous organisms. Consequently, those populations suffer from various diseases and abnormalities and finally may suddenly extinct. Moreover, any homozygous organism means zero variation, mutation-genetic drift equilibrium also creates zero variation. But variation is the raw material of evolution; so, no evolution occurs by the genetic drift. So, evolutionary biologists rejected both the genetic drift and the small populations for any kind of evolution. Hence, the Neutral theory is opposite to any kind of evolution. Again, recent experiments of ecological genetics with small populations, 12 biochemical tests, and the data of the DNA sequence, fossil evidence oppose the Neutral theory. Furthermore, the rate of evolution by the Neutral theory is equal to the rate of mutation. But mutations are opposite to any kind of evolution. So, biologists rejected the Neutral theory. As the natural selection is not justified in Nearly Neutral theory; so, Neutral theory=Nearly Neutral theory. Consequently, the rejection of the Neutral theory means the rejection of the Nearly Neutral theory. Thus, both the Neutral theory and the Nearly Neutral theory are opposite to any kind of evolution.